[College Union plaza] - P. K. Phillips::::::photographer::: (1974)
Students sit on circular, concrete benches in the College Union plaza. The benches are circular in shape with a small plant existing in the middle space of the bench. The students are sitting directly in front of the mural. Banners on the second floor mezzanine railing read: 'Coffeehouse! Sun. - Live Music,' 'Authentic Mexican [...], at the Veterans Memorial Hall, a Fashion Show, Sponsored by the [Ethnic Board?] Cal Poly,' 'May 5, 8, Visit San Diego Zoo, [....] the Escape Route.'